Okoliš i automobil - Štrumberger, Nada; Džanić, Husein (Promet - Traffic&Transportation, 2012)
Constant increase of the number of automobiles causes demand for individual materials to get on the rise, thus giving an impulse to the development of recycling logistics. Used automobiles get disassembled and individual parts which can be used as raw materials or additives get recycled. Automobile tires can be reclaimed or vulcanized. In July 1978 the environmental-friendly ’Blauer Engel’ or ’Blue Angel’ symbol was first introduced for reclaimed tires. Later, emblems were introduced for other recycled automobile pans. The awarding of the emblem is being controlled and approved by authorized institutes, because the emblem rightfully designates traffic safety.